Orthodontic Management of Crowding - case report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Two female aged 13 andl 5 yrs presented with class-I malocclusion with crowding and lock bite on upper right and left lateral incisors. Treatment involved extraction of all first premolars. The alignment of teeth of booth arch was achieved by edgewise orthodontic therapy.Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.25-30